Cell Death and Inflammation in Murine Atherosclerosis - Qian, Alexander S (My University, 2024)
Atherosclerosis, the underlying cause of cardiovascular diseases such as coronary artery disease, is driven by inflammation and cell death of leukocytes, particularly macrophages. These processes contribute significantly to plaque destabilization, leading to the development of vulnerable plaques prone to rupture and thrombotic events. Understanding the mechanisms underlying leukocyte inflammation and cell death in atherosclerosis is crucial for identifying novel therapeutic targets to stabilize plaques and reduce the risk of cardiovascular events. Proprotein convertase subtilisin/kexin type 9 (PCSK9) has emerged as a key player in atherosclerosis, with its role in lipid metabolism and plaque development being extensively studied. While PCSK9 is predominantly produced in hepatocytes, emerging evidence suggests its expression in leukocytes and macrophages may have distinct effects on atherosclerosis, beyond its role in lipid regulation. In this thesis, the role of leukocyte PCSK9 in atherosclerosis was investigated by restoring normal PCSK9 expression in leukocytes of PCSK9 and ApoE-deficient mice. Contrary to expectations, restoring leukocyte PCSK9 expression did not significantly alter plaque size, macrophage or smooth muscle cell content, pro-inflammatory cytokine expression, or apoptosis within plaques. These findings suggest that leukocyte PCSK9 expression may not significantly impact atherosclerotic plaque development or the local plaque environment in this mouse model. In this thesis, we also explored the role of ApoA1 deficiency and Bim-mediated apoptosis in atherosclerotic plaque development. ApoA1 deficiency increased plaque size, necrotic core size, and apoptosis in macrophages within plaques, potentially through upregulation of Bim protein. Inhibiting Bim in all bone marrow-derived cells and myeloid-specific cells reduced plaque apoptosis, necrotic core sizes, and plaque sizes, highlighting the significance of Bim in atherosclerosis progression, and suggesting a specific role of myeloid cell-derived Bim in plaque stability. These findings provide insights for future PCSK9 research and contribute to our understanding of HDL's protective effects and a potential therapeutic target for apoptotic cell death in atherosclerosis.
REGULATION OF CELL DEATH AND INFLAMMATION IN ATHEROSCLEROSIS: ROLES OF PCSK9, APOA1, AND BIM IN ATHEROSCLEROTIC MICE
Keywords: Atherosclerosis; Apoptosis; Inflammation; PCSK9; HDL; Macrophages